HUBBUL WATHON MINAL IMAN AND TAX COMPLIANCE INTENTION: THE MODERATING ROLE OF TAX AWARENESS - Dewi Kusuma Wardani; Ni’matul Ula Qurrotul Aini (Universitas Tulungagung, 2026)
This study aims to examine the effect of understanding hubbul wathon minal iman on prospective taxpayers’ intention to comply with tax obligations and to investigate the moderating role of tax awareness. The study employed a quantitative approach using primary data collected through questionnaires distributed to 501 Muslim prospective taxpayers in Indonesia selected through purposive and snowball sampling techniques. Data were analyzed using multiple regression and moderated regression analysis (MRA) with IBM SPSS 26. The results indicate that understanding hubbul wathon minal iman has a positive and significant effect on tax compliance intention. Furthermore, tax awareness significantly moderates and strengthens the relationship between understanding hubbul wathon minal iman and prospective taxpayers’ intention to comply taxes. These findings imply that religious and nationalist values, suppoted by high tax awareness, can encourage voluntary tax compliance among young generations. This study contributes to behavioral taxation literature by integrating local religious values within the Theory of Planned Behavior framework.